Entrepreneurship Learning Strategies and the Contribution of Teacher Behavior in Shaping Vocational High School Students' Entrepreneurial Intentions: A Literature Review - Eko Mety Setyowati; Dwi wahyudi; Sri Nurhayanti; Indah Kumoro Wati; Ahmad Happy Nashrullah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Global phenomena highlight the increasing attention to entrepreneurship as a solution to reduce unemployment and promote sustainable economic growth (SDG 8: Decent Work and Economic Growth). On a local level, vocational high school (SMK) graduates in Indonesia face the challenge of low entrepreneurial intention, which has the potential to exacerbate youth unemployment rates. This study aims to explore entrepreneurship learning strategies and the contribution of teacher behavior in shaping the entrepreneurial intentions of SMK students through a Systematic Literature Review (SLR) approach. The novelty of this research lies in integrating two key elements—innovative learning strategies and teacher behavior as role models—which have been minimally discussed in previous literature. The urgency of this research stems from its contribution to SDG 4 (Quality Education), by strengthening entrepreneurship education as a foundation for developing a competitive workforce. The method employed in this study is a Systematic Literature Review (SLR), which involves collecting and analyzing relevant journal articles using VOSviewer software based on selected keywords. The findings indicate that project-based and collaborative learning approaches enable students to directly experience real-world business challenges, such as developing business ideas and working in teams to solve practical problems. Teacher behavior, serving as both facilitator and motivator, plays a crucial role in encouraging students to dream big, believe in their abilities, and view entrepreneurship as an attractive career path. The implications of this research provide practical insights for educators and policymakers in designing effective entrepreneurship curricula while supporting the SDG agenda, particularly in promoting quality education, decent work, and inclusive economic growth. This study contributes to the reinforcement of sustainable entrepreneurship education in Indonesia.